Effect of Lipid Nanoparticle Physico-Chemical Properties and Composition on Their Interaction with the Immune System - Laura Catenacci; Rachele Rossi; Francesca Sechi; Daniela Buonocore; Milena Sorrenti; Sara Perteghella; Marco Peviani; Maria Cristina Bonferoni (Pharmaceutics)
Lipid nanoparticles (LNPs) have shown promise as a delivery system for nucleic acid-based therapeutics, including DNA, siRNA, and mRNA vaccines. The immune system plays a critical role in the response to these nanocarriers, with innate immune cells initiating an early response and adaptive immune cells mediating a more specific reaction, sometimes leading to potential adverse effects. Recent studies have shown that the innate immune response to LNPs is mediated by Toll-like receptors (TLRs) and other pattern recognition receptors (PRRs), which recognize the lipid components of the nanoparticles. This recognition can trigger the activation of inflammatory pathways and the production of cytokines and chemokines, leading to potential adverse effects such as fever, inflammation, and pain at the injection site. On the other hand, the adaptive immune response to LNPs appears to be primarily directed against the protein encoded by the mRNA cargo, with little evidence of an ongoing adaptive immune response to the components of the LNP itself. Understanding the relationship between LNPs and the immune system is critical for the development of safe and effective nucleic acid-based delivery systems. In fact, targeting the immune system is essential to develop effective vaccines, as well as therapies against cancer or infections. There is a lack of research in the literature that has systematically studied the factors that influence the interaction between LNPs and the immune system and further research is needed to better elucidate the mechanisms underlying the immune response to LNPs. In this review, we discuss LNPs’ composition, physico-chemical properties, such as size, shape, and surface charge, and the protein corona formation which can affect the reactivity of the immune system, thus providing a guide for the research on new formulations that could gain a favorable efficacy/safety profile.